The Role of The Bamboo Basket Craft Industry in Increasing The Household Income of Artisans in Sirpang Dalig Raya Village, Simalungun Regency - Meylida Nurrachmania; Sonia Somadona (Program Studi Akuntansi Universitas Simalungun, 2026)
Bamboo is one of the most important non-timber forest products (NTFPs) that has high economic potential and contributes to improving rural livelihoods through value-added processing. In Sirpang Dalig Raya Village, Simalungun Regency, bamboo basket handicrafts have become one of the primary economic activities for local households. However, information regarding the income generated from this business, its contribution to total household income, and its role in improving household welfare remains limited. This study aimed to calculate the income generated from the bamboo basket handicraft business, analyze its contribution to the total household income of artisans, and describe its role in increasing household income in Sirpang Dalig Raya Village, Simalungun Regency. The research employed a quantitative descriptive approach. Data were collected through structured interviews and direct observations involving 190 bamboo basket artisans selected using purposive sampling. Data were analyzed using production cost analysis, revenue analysis, income analysis, and contribution analysis. The results showed that the average production cost of the bamboo basket business was IDR 4,455,000 per production period, consisting of IDR 50,000 in fixed costs and IDR 4,405,000 in variable costs. With an average production of 500 baskets and a selling price of IDR 20,000 per basket, the average total revenue reached IDR 10,000,000, resulting in a net income of IDR 5,545,000 per production period. The bamboo basket business contributed 61.72% to the total household income, making it the primary source of income compared with agriculture, rubber tapping, livestock farming, wage labor, and small-scale trading. These findings indicate that bamboo basket handicrafts play a significant role in increasing household income, creating employment opportunities, and supporting sustainable rural economic development through the utilization of non-timber forest products